PENGARUH RETURN ON ASSET, BIAYA OPERASIONAL ATAS PENDAPATAN OPERASIONAL, FINANCING TO DEPOSIT RATIO, DAN NON PERFORMING FINANCING TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH (Studi Empiris pada Bank Umum Syariah di Indonesia Periode 2012-2015) - Fadilawati, Nuri; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to examine the effect of ROA (Return on Asset), BOPO (Operating Expenses to Operating Income), FDR (Financing to Deposit Ratio), and NPF (Non Performing Financing) to level of profit sharing mudharabah deposit of Islamic banks in Indonesia for the period of 2012-2015. The technique that used in this study is purposive sampling. From 12 Islamic banks listed in BI (Indonesia Bank) in 2012-2015, 11 Islamic banks are choosed as the sample in this study. The type of data used in this study is secondary which is financial statement. The analysis technique used in this study is multiple linear regression using IBM SPSS (Statistical Package fo Social Science) 20th version program. The result of the study show that ROA, BOPO, FDR, and NPF silmutaneously have significant effect on level of profit sharing mudharabah deposit. Partial results show that ROA have no effect on level of profit sharing mudharabah deposit, BOPO have significant negative effect, FDR have significant positive effect, and NPF have significant negative effect on level of profit sharing mudharabah deposit.